Using game engines in ray tracing physics (2010)
This paper shows the used of a complete open source game engine and the significant advanced in computer graphics for applied ray tracing physics techniques in urban environment of propagation. We used techniques and software developed for open source game engine to: 1) The ray tracing physics algorithm for path loss, reflection and multiple diffraction. 2) The efficient use of graphic processing unit (GPU) and the multiple processor of the CPU.